M-NiFe LDH catalyst and application of M-NiFe LDH catalyst in electro-catalysis biomass oxidative coupling hydrogen production
By using M-NiFe LDH catalyst in electrocatalytic biomass oxidation coupled hydrogen production, MoO42- is inserted between layers and oxygen vacancy defects are constructed, the problem of slow kinetics of the anode oxygen evolution reaction is solved, and efficient hydrogen production and biomass oxidation reaction is achieved, and high value-added chemical raw materials are produced.
Patent Information
- Application Number
- CN202510110282.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-09
AI Technical Summary
The prior art is limited by the slow kinetics of anode oxygen evolution reaction (OER) in electrocatalytic biomass oxidative coupled hydrogen production, resulting in low catalytic efficiency.
The M-NiFe LDH catalyst was used to insert high-valent metal anion MoO42-regulated electronic structure between layers, expand the layer spacing and expose more active sites, and oxygen vacancies were constructed by CV cycle reduction method to improve catalytic activity and selectivity.
A highly efficient oxidation reaction of biomass 5-hydroxymethylfurfural is achieved, which maximizes hydrogen production efficiency, reduces costs, and produces a high-value-added chemical raw material 2,5-furandicarboxylic acid.
Smart Images

Figure CN119956394A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen preparation and catalyst materials, and particularly relates to an M-NiFe LDH catalyst and application thereof in electrocatalytic biomass oxidation coupled hydrogen production. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Hydrogen production by water electrolysis has become the most promising green hydrogen production technology due to its mild conditions and abundant raw materials. However, it is limited by the slow kinetics of the oxygen evolution reaction (OER) at the anode. Therefore, attempts have been made to replace the anode oxygen evolution reaction with some more thermodynamically favorable organic small molecule oxidation reactions to achieve efficient coupled hydrogen production.
[0004] Electrocatalytic 5-hydroxymethylfurfural oxidation reaction (HMFOR) provides a promising strategy to convert biomass derivatives into high value-added chemicals. Using HMFOR reaction instead of OER reaction as the anode reaction and coupling it with the hydrogen evolution reaction (HER) at the cathode can not only effectively reduce the anode oxidation voltage, but also produce 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural oxidation, which is an important biomass value-added chemical and can be used as a key precursor for the preparation of green and biodegradable bio-based polyesters as PTA substitutes.
[0005] Currently, transition metal double-layer hydroxides (LDHs) have been shown to show great potential in HMF electrooxidation due to their flexible electronic structure and low cost. - The competitive adsorption and coupling process of hydroxymethylfurfural are hindered, resulting in reduced catalytic efficiency. Therefore, it is an urgent problem for those skilled in the art to develop a catalyst that can promote the highly active and highly selective electrocatalytic 5-hydroxymethylfurfural oxidation reaction and achieve efficient coupled hydrogen production. Summary of the invention
[0006] In view of the needs of the prior art, the purpose of the present invention is to provide an M-NiFe LDH catalyst and its application in electrocatalytic biomass oxidation coupled hydrogen production. The biomass oxidation coupled hydrogen production system constructed by the present invention can produce hydrogen efficiently at the cathode while electro-oxidizing biomass 5-hydroxymethylfurfural at the anode to produce high value-added chemical raw material 2,5-furandicarboxylic acid, thereby maximizing the hydrogen production efficiency; and can insert high-valent metal anions (MO4 2-), regulating the electronic structure to improve the catalytic activity of HMFOR, expanding the interlayer spacing to expose more active sites, and at the same time, by further utilizing the CV cycle reduction method to construct oxygen vacancy defects, achieve rapid generation and content control of oxygen vacancies, and attract OH - Filling oxygen vacancies to improve the reaction selectivity of HMFOR.
[0007] Specifically, the present invention provides the following technical solutions:
[0008] In a first aspect of the present invention, there is provided an M-NiFe LDH catalyst, wherein the M-NiFe LDH catalyst comprises a NiFe LDH catalyst and MO4 intercalated therein. 2- , wherein M is selected from one or more of Mo, W, V, and Cr.
[0009] Preferably, the M-NiFe LDH catalyst is an oxygen-deficient M-NiFe LDH catalyst, and the oxygen defect is prepared on the surface of the M-NiFe LDH catalyst by cyclic voltammetry scanning.
[0010] Preferably, the M-NiFe LDH catalyst is obtained by in-situ growth on the surface of a substrate, and the substrate is selected from one or more of foamed nickel, carbon paper, foamed iron, and carbon cloth.
[0011] Preferably, the cyclic voltammetry scan is performed using the M-NiFe LDH catalyst as the working electrode, the graphite sheet as the counter electrode and Hg / HgO as the reference electrode.
[0012] The second aspect of the present invention provides a method for preparing the above-mentioned M-NiFe LDH catalyst, specifically: mixing nickel salt, iron salt, ammonium salt, CO(NH2)2, NH4F and a substrate, and conducting a hydrothermal reaction to obtain the M-NiFe LDH catalyst.
[0013] Preferably, the M-NiFe-LDH catalyst is used as a working electrode, a graphite sheet is used as a counter electrode and Hg / HgO is used as a reference electrode, and a cyclic voltammetry scan is performed to obtain an oxygen-deficient M-NiFe LDH catalyst (Vo-M-NiFe LDH).
[0014] Preferably, the molar ratio of the nickel salt, iron salt, ammonium salt, CO(NH2)2, and NH4F is 0.25-0.35:0.08-0.12:0.08-0.12:2.8-3.2:0.8-1.2; further preferably, the molar ratio of the nickel salt, iron salt, ammonium salt, CO(NH2)2, and NH4F is 0.3:0.1:0.1:3:1.
[0015] Preferably, the nickel salt includes nickel nitrate hexahydrate, the iron salt includes ferric nitrate nonahydrate, and the ammonium salt includes ammonium molybdate, ammonium tungstate, ammonium metavanadate, and ammonium chromate.
[0016] Preferably, the substrate is added after pretreatment, and the pretreatment is: washing and drying the substrate in sequence, wherein the washing includes alkali washing and water washing.
[0017] Preferably, the temperature of the hydrothermal reaction is 100-150°C, and the time is 10-24 hours; the product after the hydrothermal reaction also needs to be washed and dried, wherein the washing includes alkali washing and water washing, and the drying temperature is 50-70°C, and the time is 10-24 hours.
[0018] Preferably, the scanning window of the cyclic voltammetry scanning is 0 to -1.4 V, the number of scanning cycles is 3 to 10, and the scanning rate is 3 to 5 mV s -1 .
[0019] The third aspect of the present invention provides an application of the M-NiFe LDH catalyst described in the first aspect in electrocatalytic biomass oxidation coupled hydrogen production.
[0020] Preferably, the electrolyte in the electrocatalysis is a mixed solution of potassium hydroxide and 5-hydroxymethylfurfural, the concentration of potassium hydroxide is 1 to 3 M, and the concentration of 5-hydroxymethylfurfural is 8 to 12 mM.
[0021] The beneficial effects achieved by one or more of the above technical solutions of the present invention are as follows:
[0022] (1) The present invention proposes a method for producing hydrogen by coupling oxidation of 5-hydroxymethylfurfural from anode biomass, which effectively avoids the problem of high thermodynamic barrier of anode oxygen evolution reaction (OER), maximizes hydrogen production efficiency, reduces costs, and the product 2,5-furandicarboxylic acid can be obtained at the anode, which is one of the important bio-based chemical raw materials and has excellent industrial application prospects.
[0023] (2) The present invention proposes a MoO4 2- The synthesis method of anion intercalated NiFe LDH catalyst is compared with CO3 2- Intercalation, MoO4 2- The introduction of MoO4 can effectively adjust the electronic structure of Ni and Fe and improve the activity by increasing the oxidation state. 2- Compared to CO3 2- The large size can increase the interlayer spacing of NiFe LDH and expose more active sites.
[0024] (3) The present invention proposes a method for constructing oxygen vacancy defects under mild and controllable conditions. The oxygen defects are constructed on the surface of NiFe LDH catalyst by performing CV cycles in the reduction potential window. The method is simple and controllable, and the conditions are mild. While utilizing oxygen vacancy defects to improve the HMFOR reaction activity and adsorption selectivity, serious damage to the catalyst material structure is avoided. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 1 is the XRD pattern of the Mo-NiFe LDH prepared in Example 1 and the NiFe LDH prepared in Comparative Example 1;
[0027] Figure 2 1 is the SEM spectrum of the Mo-NiFe LDH prepared in Example 1 and the NiFe LDH prepared in Comparative Example 1;
[0028] Figure 3 1 is a Raman spectrum of the Mo-NiFe LDH prepared in Example 1 and the NiFe LDH prepared in Comparative Example 1;
[0029] FIG4( a) is an XPS spectrum of Mo-NiFe LDH prepared in Example 1;
[0030] FIG4( b ) is an XPS spectrum of NiFe LDH prepared in Comparative Example 1;
[0031] Figure 5 are EPR spectra of the Mo-NiFe LDH prepared in Example 1, the Vo-Mo-NiFe LDH-3 prepared in Example 2, the Vo-Mo-NiFe LDH-5 prepared in Example 3, and the Vo-NiFe LDH-3 catalyst prepared in Comparative Example 2;
[0032] Figure 6 The linear sweep voltammetry curves of Examples 1 to 3 and Comparative Examples 1 to 2 in 1M KOH+10mM HMF electrolyte;
[0033] Figure 7 This is the system diagram of biomass HMF oxidation coupled hydrogen production;
[0034] Figure 8 is a comparison diagram of linear sweep voltammetric curves of Example 3 in different electrolytes;
[0035] Fig. 9 It is a comparison chart of the catalytic performance of the samples prepared in Example 3 and Comparative Example 1. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0037] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0038] Example 1 :This embodiment provides a Mo-NiFe LDH catalyst and a preparation method thereof
[0039] (1) A nickel foam with a thickness of 0.5 mm was cut into a standard rectangle of 2 cm*4 cm, and ultrasonically cleaned with 3M KOH, ethanol, and deionized water in sequence for 10 min, and then dried.
[0040] (2) The nickel foam substrate pretreated in step (1) was placed in 30 mL of deionized water containing Ni(NO3)2·6H2O (0.9 mmol), Fe(NO3)3·9H2O (0.3 mmol), (NH4)2MoO4 (0.3 mmol), CO(NH2)2 (9 mmol) and NH4F (3 mmol), and stirred at room temperature for about 1 h.
[0041] (3) The mixture stirred in step (2) was placed in a 50 mL Teflon line stainless steel autoclave and kept at 120°C for 12 h. After cooling to room temperature, the surface in-situ grown MoO4 2- The nickel foam of intercalated NiFe LDH (named Mo-NiFe LDH) was repeatedly rinsed with ethanol and deionized water. Then, it was placed in a vacuum drying oven at 60°C for 12 h to obtain reddish-brown MoO4 2- Intercalated NiFe LDH catalyst (Mo-NiFe LDH).
[0042] Example 2 :This embodiment provides an oxygen-deficient Mo-NiFe LDH catalyst and a preparation method thereof
[0043] (1) A nickel foam with a thickness of 0.5 mm was cut into a standard rectangle of 2 cm*4 cm, and ultrasonically cleaned with 3M KOH, ethanol, and deionized water in sequence for 10 min, and then dried.
[0044] (2) The nickel foam substrate pretreated in step (1) was placed in 30 mL of deionized water containing Ni(NO3)2·6H2O (0.9 mmol), Fe(NO3)3·9H2O (0.3 mmol), (NH4)2MoO4 (0.3 mmol), CO(NH2)2 (9 mmol) and NH4F (3 mmol), and stirred at room temperature for about 1 h.
[0045] (3) The mixture stirred in step (2) was placed in a 50 mL Teflon line stainless steel autoclave and kept at 120°C for 12 hours. After cooling to room temperature, the surface in-situ grown MoO4 2- The nickel foam of intercalated NiFe LDH (named Mo-NiFe LDH) was repeatedly rinsed with ethanol and deionized water. Then, it was placed in a vacuum drying oven at 60°C for 12 h to obtain reddish-brown MoO4 2- Intercalated NiFe LDH catalyst (Mo-NiFe LDH).
[0046] (4) CV cycles were performed in 1 mol / L KOH using a three-electrode system on a Metrohm Autolab electrochemical workstation. The Mo-NiFe LDH, graphite sheet and Hg / HgO prepared in step (3) were used as the working electrode, counter electrode and reference electrode, respectively. The scan window was 0 to -1.2 V (vs. RHE) and the scan rate was 5 mV s -1 Oxygen vacancy defect NiFeLDH catalyst (Vo-Mo-NiFe LDH-3) was obtained.
[0047] Example 3 :This embodiment provides an oxygen-deficient Mo-NiFe LDH catalyst and a preparation method thereof
[0048] (1) A nickel foam with a thickness of 0.5 mm was cut into a standard rectangle of 2 cm*4 cm, and ultrasonically cleaned with 3M KOH, ethanol, and deionized water in sequence for 10 min, and then dried.
[0049] (2) The nickel foam substrate pretreated in step (1) was placed in 30 mL of deionized water containing Ni(NO3)2·6H2O (0.9 mmol), Fe(NO3)3·9H2O (0.3 mmol), (NH4)2MoO4 (0.3 mmol), CO(NH2)2 (9 mmol) and NH4F (3 mmol), and stirred at room temperature for about 1 h.
[0050] (3) The mixture stirred in step (2) was placed in a 50 mL Teflon line stainless steel autoclave and kept at 120°C for 12 hours. After cooling to room temperature, the surface in-situ grown MoO42- The nickel foam of intercalated NiFe LDH (named Mo-NiFe LDH) was repeatedly rinsed with ethanol and deionized water. Then, it was placed in a vacuum drying oven at 60°C for 12 h to obtain reddish-brown MoO4 2- Intercalated NiFe LDH catalyst (Mo-NiFe LDH).
[0051] (4) CV cycles were performed in 1 mol / L KOH using a three-electrode system on a Metrohm Autolab electrochemical workstation. The Mo-NiFe LDH, graphite sheet and Hg / HgO prepared in step (3) were used as the working electrode, counter electrode and reference electrode, respectively. The scan window was 0 to -1.2 V (vs. RHE) and the scan rate was 5 mV s -1 Oxygen vacancy defect NiFeLDH catalyst (Vo-Mo-NiFe LDH-5) was obtained.
[0052] Comparative Example 1 :This comparative example provides a NiFe LDH catalyst and a preparation method thereof
[0053] (1) A nickel foam with a thickness of 0.5 mm was cut into a standard rectangle of 2 cm*4 cm, and ultrasonically cleaned with 3M KOH, ethanol, and deionized water in sequence for 10 min, and then dried.
[0054] (2) The nickel foam substrate pretreated in step (1) was placed in 30 mL of deionized water containing Ni(NO3)2·6H2O (0.9 mmol), Fe(NO3)3·9H2O (0.3 mmol), CO(NH2)2 (9 mmol) and NH4F (3 mmol), and stirred at room temperature for about 1 h.
[0055] (3) The mixture stirred in step (2) was placed in a 50 mL Teflon line stainless steel autoclave and kept at 120° C. for 12 hours. After cooling to room temperature, the nickel foam with a NiFe LDH film on the surface (named NiFe LDH) was repeatedly rinsed with ethanol and deionized water. Then, it was placed in a vacuum drying oven at 60° C. for 12 hours to obtain a reddish brown NiFe LDH catalyst.
[0056] Comparative Example 2 :This comparative example provides an oxygen-deficient NiFe LDH catalyst and a preparation method thereof
[0057] (1) A nickel foam with a thickness of 0.5 mm was cut into a standard rectangle of 2 cm*4 cm, and ultrasonically cleaned with 3M KOH, ethanol, and deionized water in sequence for 10 min, and then dried.
[0058] (2) The nickel foam substrate pretreated in step (1) was placed in 30 mL of deionized water containing Ni(NO3)2·6H2O (0.9 mmol), Fe(NO3)3·9H2O (0.3 mmol), CO(NH2)2 (9 mmol) and NH4F (3 mmol), and stirred at room temperature for about 1 h.
[0059] (3) The mixture stirred in step (2) was placed in a 50 mL Teflon line stainless steel autoclave and kept at 120° C. for 12 hours. After cooling to room temperature, the nickel foam with a NiFe LDH film on the surface (named NiFe LDH) was repeatedly rinsed with ethanol and deionized water. Then, it was placed in a vacuum drying oven at 60° C. for 12 hours to obtain a reddish brown Vo-NiFe LDH catalyst.
[0060] (4) CV cycles were performed in 1 mol / L KOH using a three-electrode system on a Metrohm Autolab electrochemical workstation. The Vo-NiFe LDH, graphite sheet and Hg / HgO prepared in step (3) were used as the working electrode, counter electrode and reference electrode, respectively. The scan window was 0 to -1.2 V (vs. RHE) and the scan rate was 5 mV s -1 Oxygen vacancy defect NiFeLDH catalyst (Vo-NiFe LDH-3) was obtained.
[0061] Test Example 1 :
[0062] In this test example, a powder X-ray diffractometer, a scanning transmission electron microscope and a Raman spectrum were used to observe the crystal structure and morphology characteristics of the catalysts prepared in Example 1 and Comparative Example 1.
[0063] like Figure 1 As shown in FIG. 1 , the XRD patterns of the Mo-NiFe LDH catalyst prepared in Example 1 and the NiFe LDH catalyst prepared in Comparative Example 1 are shown. It can be seen that the diffraction peaks correspond to the characteristic peaks of NiFe LDH (PDF#40-0215), which confirms that the catalysts synthesized in Comparative Example 1 and Example 1 are the crystal structures of nickel-iron layered double hydroxides, and it is found that the introduction of high-valent interlayer anions MoO4 2- After that, the diffraction peak intensity decreases, the crystallinity decreases, and the diffraction peak shifts slightly to the left, indicating that the interlayer spacing increases.
[0064] like Figure 2 , which are SEM images of the Mo-NiFe LDH catalyst prepared in Example 1 and the NiFe LDH catalyst prepared in Comparative Example 1. It can be seen that the morphology of the catalysts synthesized in Comparative Example 1 and Example 1 is a flower-like structure composed of nanosheets.
[0065] like Figure 3 As shown in the figure, the Raman spectra of the Mo-NiFe LDH catalyst prepared in Example 1 and the NiFe LDH catalyst prepared in Comparative Example 1 show that the Raman spectra at 453 and 531 cm -1 The characteristic peak at 910cm -1 and 1060cm -1 The peaks at 2- and CO3 2- The characteristic peaks of MoO4 2- Introduction in NiFe LDH.
[0066] Test Example 2 :
[0067] In this test example, X-ray photoelectron spectroscopy (XPS) was used to observe the electronic structures of Example 1 and Comparative Example 1; and electron paramagnetic resonance (EPR) was used to observe the unpaired electron states of Examples 1 to 3 and Comparative Example 2, respectively.
[0068] As shown in FIG4 , the XPS spectra of the Mo-NiFe LDH catalyst prepared in Example 1 and the NiFe LDH catalyst prepared in Comparative Example 1 are shown, wherein FIG4 (a) is the Ni 2p spectrum and FIG4 (b) is the Fe 2p spectrum. It can be seen that the introduction of high-valent metal anions MoO4 2- Afterwards, the high valence state of Mo affects the electronic structure of Ni and Fe, the characteristic peaks of Ni and Fe shift to the left, and the oxidation state increases, which can effectively improve their catalytic activity.
[0069] like Figure 5 As shown, Figure 5 It is the EPR spectra of the Mo-NiFe LDH prepared in Example 1, the Vo-Mo-NiFe LDH-3 prepared in Example 2, the Vo-Mo-NiFe LDH-5 prepared in Example 3 and the Vo-NiFe LDH-3 catalyst prepared in Comparative Example 2.
[0070] By comparing Examples 1 to 3, it can be seen that after a certain number of CV cycle scans at the reduction potential, there is a strong EPR signal at g=2.003, corresponding to the formation of oxygen vacancy defects, and it is found that as the number of cycles increases from 3 to 5, the signal becomes stronger and more oxygen vacancy defects exist.
[0071] By comparing Example 2 and Comparative Example 2, it is found that MoO4 2- After the introduction, the oxygen vacancy content after CV cycle reduction is higher, indicating that MoO4 2- The introduction of is conducive to the formation of oxygen vacancies, and it is speculated that MoO4 2-There is precipitation in KOH solution, which destroys the structural stability and is more conducive to the generation of oxygen vacancies.
[0072] Test Example 3 :
[0073] In order to evaluate the activity of a series of prepared NiFe LDH catalysts in oxygen evolution reaction (OER) and 5-hydroxymethylfurfural oxidation reaction (HMFOR) under alkaline conditions, the electrochemical performance tests were carried out respectively. The specific test steps and results are as follows:
[0074] 1. In 1M KOH+10mM HMF solution, a graphite sheet was used as a counter electrode, Hg / HgO was used as a reference electrode, and Examples 1 to 3 or Comparative Examples 1 to 2 were used as working electrodes, respectively. The three-electrode mode was used for testing. Linear voltammetric scanning was performed in the potential range of 1.0 to 1.8 V (vs. RHE) at a scanning rate of 10 mV s -1 , record the LSV curve.
[0075] like Figure 6 As shown, by comparing the catalytic performance of Example 1, Example 2, and Example 3, it is found that after CV cycle scanning, the reduction potential leads to the generation of oxygen vacancy defects, and the presence of oxygen vacancy defects attracts OH- to be adsorbed and filled preferentially, thereby avoiding competitive adsorption of HMF and OH- at the active sites and improving the catalytic selectivity; at the same time, by controlling the number of CV cycles, the oxygen vacancy content can be controlled, thereby effectively improving the catalytic performance and avoiding serious damage to the NiFe LDH structure.
[0076] Observe the comparative example 1 and the example 1, before the CV cycle reduction, MoO4 2- The introduction of MoO4 can improve the catalytic activity, which may be due to the fact that the introduction of high-valent metal anions can regulate the electronic structure of Ni and Fe sites, improve the oxidizability of Ni and Fe, and improve the catalytic activity of active sites, as shown in the XPS of Figure 4; on the other hand, it may be due to the fact that MoO4 2- Compared to CO3 2- The large size of the nanostructures increases the interlayer spacing and exposes more active sites, such as Figure 1 XRD pattern shown.
[0077] Observing Example 2 and Comparative Example 2, it is found that after CV cycles, MoO4 2- The introduction of Figure 5 Compared with the oxygen vacancy content measured by the EPR spectrum shown in the figure, it is found that MoO4 2- The introduction of is conducive to the generation of oxygen vacancy defects.
[0078] 2. Example 3 is the working electrode, the graphite sheet electrode is the counter electrode, and the Hg / HgO electrode is the reference electrode. The three-electrode mode is used for testing in 1M KOH solution (PH=14) and 1M KOH+10mM HMF solution, respectively. Linear voltammetric scanning is performed in the potential range of 1.0-1.8V (vs.RHE) at a scanning rate of 10mV s -1 , record the LSV curve.
[0079] like Figure 8 As shown, it is a comparison diagram of the linear sweep voltammetric curves of Example 3 in different electrolytes. It can be seen that after the introduction of HMF, the current density is significantly improved, indicating the superiority of constructing a biomass HMF oxidation coupled hydrogen evolution system. Compared with the traditional coupling of oxygen evolution reaction (OER) and hydrogen evolution reaction (HER), the biomass coupled hydrogen production system greatly reduces the hydrogen production energy barrier, reduces power consumption, and improves hydrogen production efficiency.
[0080] 3. In addition, Example 3 and Comparative Example 1 were oxidized in 1M KOH+10mM HMF electrolyte for the same time, and high performance liquid chromatography (HPLC) was used for qualitative and quantitative analysis to calculate the HMF conversion rate, FDCA yield and Faradaic efficiency (FE). Figure 7 As shown, it is a system diagram of biomass HMF oxidation coupled hydrogen production; Fig. 9 As shown, it was found that the Vo-Mo NiFe LDH prepared by introducing high-valent metal anions and controlling the generation of oxygen vacancy defects had higher HMF conversion and FDCA yield.
[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An M-NiFe LDH catalyst, characterized in that: The M-NiFe LDH catalyst comprises a NiFe LDH catalyst and an intercalated MO4 2- , wherein M is selected from one or more of Mo, W, V, and Cr.
2. The M-NiFe LDH catalyst according to claim 1, characterized in that The M-NiFe LDH catalyst is an oxygen-deficient M-NiFe LDH catalyst, and the oxygen defect is prepared on the surface of the M-NiFe LDH catalyst by cyclic voltammetry scanning.
3. The M-NiFe LDH catalyst according to claim 1, characterized in that The M-NiFe LDH catalyst is obtained by in-situ growth on the surface of a substrate, and the substrate is selected from one or more of foamed nickel, carbon paper, foamed iron, and carbon cloth.
4. The M-NiFe LDH catalyst according to claim 2, characterized in that The cyclic voltammetry scan was performed with the M-NiFeLDH catalyst as the working electrode, the graphite sheet as the counter electrode and Hg / HgO as the reference electrode.
5. A method for preparing the M-NiFe LDH catalyst according to any one of claims 1 to 4, characterized in that: Specifically, nickel salt, iron salt, ammonium salt, CO(NH2)2, NH4F and substrate are mixed and subjected to hydrothermal reaction to obtain M-NiFe LDH catalyst.
6. The preparation method according to claim 5, characterized in that: The M-NiFe-LDH catalyst was used as a working electrode, a graphite sheet was used as a counter electrode and Hg / HgO was used as a reference electrode, and a cyclic voltammetry scan was performed to obtain an oxygen-deficient M-NiFe LDH catalyst.
7. The preparation method according to claim 5, characterized in that: The molar ratio of the nickel salt, iron salt, ammonium salt, CO(NH2)2, and NH4F is 0.25-0.35:0.08-0.12:0.08-0.12:2.8-3.2:0.8-1.2; preferably, the molar ratio of the nickel salt, iron salt, ammonium salt, CO(NH2)2, and NH4F is 0.3:0.1:0.1:3:1; Wherein, the nickel salt includes nickel nitrate hexahydrate, the iron salt includes iron nitrate nonahydrate, and the ammonium salt includes ammonium molybdate, ammonium tungstate, ammonium metavanadate, and ammonium chromate; Preferably, the substrate is added after pretreatment, and the pretreatment is: washing and drying the substrate in sequence, wherein the washing includes alkali washing and water washing; Preferably, the temperature of the hydrothermal reaction is 100-150°C, and the time is 10-24 hours; the product after the hydrothermal reaction also needs to be washed and dried, wherein the washing includes alkali washing and water washing, and the drying temperature is 50-70°C, and the time is 10-24 hours.
8. The preparation method according to claim 6, characterized in that: The scanning window of the cyclic voltammetry scanning is 0 to -1.4 V, the scanning number is 3 to 10, and the scanning rate is 3 to 5 mV s -1 .
9. Use of the M-NiFe LDH catalyst according to any one of claims 1 to 4 in electrocatalytic biomass oxidation coupled hydrogen production.
10. The use according to claim 9, characterized in that The electrolyte in the electrocatalysis is a mixed solution of potassium hydroxide and 5-hydroxymethylfurfural, the concentration of the potassium hydroxide is 1-3M, and the concentration of the 5-hydroxymethylfurfural is 8-12mM.
Citation Information
Patent Citations
Method for rapidly preparing NiFe-LDH / FeOOH catalyst to electrocatalytically oxidize HMF
CN115747865A
Nickel-iron oxyhydroxide oxygen evolution electrode and preparation method thereof
CN116005192A
Method for preparing NiFe-LDH nanosheet efficient oxygen evolution catalyst through surface reconstruction
CN117187855A
Universal One-Step Method to Make Fe-Based (Oxy)Hydroxides as Efficient OER Catalysts for Seawater Electrolysis
US20230010138A1